Wypłata dywident jako wyznacznik inwestycji w akcje spółek giełdowych - Wypych, Mirosław (Divident Payment as an Encouragement to Stock Shares Investment, 2006)
Private capital and common duty to reward capital owners for their investments is one of the market economy features. Such an obligation also applies to stock shares investments. Financial profits from the ownership of shares depend on share price rising and amount of dividend payment. Unless the company can control changes of the share prices directly, dividend payment is a result of company's net profit division. It follows that public stock company's dividend policy can affect investment decisions on stock market. It happens because stock market investors analyzing actual dividend policy try to execute their investment strategies. The goal of this paper is to present the dividend based investment strategy on public stock market and verify it in the light of efficiency. Theoretical arguments are illustrated by a few empirical examples taken from Warsaw Stock Exchange.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 737-746